H. G. Adler (1910-1988) Privatgelehrter und freier Schriftsteller. Eine Monographie - Hocheneder, Franz (2009)
The result of my extensive research project is the first comprehensive study on the life and work of H. G. Adler, an important member of the circle around Elias and Veza Canetti, Erich Fried etc., whose ground-breaking scholarly work long overshadowed his reputation as a creative writer. Adler, a German-Jewish writer, born in Prague in 1910, was the inmate of various National Socialist concentration camps (Theresienstadt, Auschwitz) during the Second World War and lived in exile in London from 1947 until his death in 1988. Both as a scholar and as a creative writer, this prolific author is one of the most interesting and most versatile personalities in postwar history. In addition to publishing seminal works on the Holocaust, he left behind an important and to a large extent unpublished body of work, consisting of narrative prose, poetry and drama as well as scholarly articles and books on history, sociology, politics, psychology, language and literature, music, arts, philosophy, theology and Jewish studies. The works of H. G. Adler address central contemporary concerns, cover a large number of areas of interest (European cultural and intellectual history, 20th century German literature, exile studies, Holocaust research etc.) and shall thus - so I hope - attract considerably more attention in the future. This monograph attempts to close a major gap in exile studies that has often been complained about in the past. Its most important topical areas are: H. G. Adler's biography, Theresienstadt (Terezín), exile in England, the development and interdependence of scholarly work and literature, H. G. Adler's position amongst writers such as Karl Kraus, Franz Kafka, George Orwell, Elias Canetti and W. G. Sebald, H. G. Adler as Franz Baermann Steiner's literary executor, H. G. Adler's position amongst London émigrés, H. G. Adler and Austria (despite his exile in England, Adler throughout his life remained closely associated with Austrian culture). This study focuses on Adler's most important and best known works "Theresienstadt 1941-1945" and "Die verheimlichte Wahrheit", books and articles like "Die Dichtung der Prager Schule" and "Der Kampf gegen die 'Endlösung der Judenfrage'", which have hitherto been neglected by academic research, the voluminous autobiographically structured or autobiographically influenced novels "Panorama", "Eine Reise" and "Die unsichtbare Wand" as well as numerous unpublished texts, documents and photographs from Adler's literary estate. It is rounded off by a complete bibliography of H. G. Adler's publication from 1947 to 1988. The time for a monograph about H. G. Adler is ideal: 2008 - 20th anniversary of H. G. Adler's death; 2010 - H. G. Adler's 100th birthday.